From liposomes to cells: Filling the gap between physicochemical and microbiological studies of the activity and selectivity of host‐defense peptides. Issue 5 (13th February 2018) - Savini, Filippo; Bobone, Sara; Roversi, Daniela; Mangoni, Maria Luisa; Stella, Lorenzo
Abstract: Host‐defense peptides (HPDs) are bactericidal and immunomodulatory molecules, part of the innate immune system of many organisms, including man. They kill bacteria mostly by perturbing their membranes, and for this reason they are a promising class of molecules to fight drug‐resistant microbes. However, their success towards clinical application is still limited, partly due to many unanswered questions on their activity and function. Our current understanding of HDPs has been reached by two parallel, but largely independent, approaches: microbiological studies on HDP effects on cells, and physicochemical investigations on model membranes. All current models for the mechanisms of HDP membrane perturbation and cell selectivity were derived from the latter kind of studies, but their relevance for real cells still had to be demonstrated. In the last few years, several studies led to quantitative insights into HDP behavior directly in cells: membrane‐binding and peptide‐induced pores in bacteria and liposomes were compared; the number of cell‐bound peptide molecules needed to kill a bacterium was determined; the variation of peptide activity and toxicity with the density of cells was characterized; selectivity was examined in a mixture of target and host cells; the sequence of events leading to bacterial death was observed in real time by microscopy on single cells. Overall, these approaches led to a new understanding of HDPs that will be helpful for their development into effective antibiotic drugs. Abstract :